加入世界贸易组织对中国汽车产业的影响及对策 = WTO & China's automobile industry : impacts & countermeasures - 杨杞 Yang, Qi (2008)
This study focuses on the impact of China’s entrance to WTO on her automobile industry. The analysis is based on several aspect: industry scale economy, labor productivity, and research and development ability, which are on the basis of the economic theories of Industrial Organization and Industrial Policy.